The synthesis of cyclic hydroxy-phosphonate bearing polybutene using ROMP - Cetinkaya, Ilay Ceren; Eren, Tarik (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
The synthesis of cyclic hydroxy-phosphonate bearing polybutenes using ring-opening metathesis polymerization (ROMP) has been accomplished. Reacting cyclooct-5-ene-1,2-diol with diethyl chlorophosphate gave a new monomer, cyclic hydroxy-phosphonate functional cyclooctene (IV). A kinetic study of the ROMP of (IV) using Grubb's second generation (G2) and third generation (G3) catalysts was carried out using H-1 NMR spectroscopy. The G2 catalyst was more efficient than G3 and gave similar to 85% conversion over 1 h at ambient temperature. Kinetic constants are also calculated and reported. At the same time, cyclooctadiene (COD) was introduced as the co-monomer in a co-polymerization route, and the characterization and thermal properties of the resulting product were investigated using NMR, GPC, TGA and DSC. Homopolymer IV gave a 37% char yield at 600 degrees C under nitrogen. Upon increasing the phosphorus content in the co-polymer also enhanced the thermal properties. This polymer has also been explored for Cu purification under both liquid-liquid and solid liquid extraction.
Keywords: OPENING-METATHESIS POLYMERIZATION; RUTHENIUM-BASED CATALYST; FREE FLAME RETARDANTS; ASYMMETRIC-SYNTHESIS; OLEFIN METATHESIS; MALEIC-ANHYDRIDE; ALPHA-AMINO; ACID; POLYMERS; EXTRACTION; Polymer Science